2006
DOI: 10.1345/aph.1g217
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Analgesia as a Potential New Therapeutic Option in the Treatment of Chronic Pain

Abstract: Cannabinoids provide a potential approach to pain management with a novel therapeutic target and mechanism. Chronic pain often requires a polypharmaceutical approach to management, and cannabinoids are a potential addition to the arsenal of treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 61 publications
1
37
0
2
Order By: Relevance
“…There are numerous case reports on the beneficial effects of cannabis or synthetic derivatives of THC in pain associated with multiple sclerosis, cancer, neuropathies, and HIV infection (Noyes et al, 1975a,b;Martyn et al, 1995;Consroe et al, 1997;Hamann and di Vadi, 1999;Ware et al, 2003;Rudich et al, 2003;Ware and Beaulieu, 2005;Berlach et al, 2006; reviewed in Burns and Ineck, 2006) (Table 1). The results of randomized studies conducted before 1999 on the analgesic effect of orally administered synthetic cannabinoids in patients with postoperative, post-traumatic, cancer, or spastic pain had been subjected to a meta-analysis.…”
Section: B Pain and Inflammationmentioning
confidence: 99%
“…There are numerous case reports on the beneficial effects of cannabis or synthetic derivatives of THC in pain associated with multiple sclerosis, cancer, neuropathies, and HIV infection (Noyes et al, 1975a,b;Martyn et al, 1995;Consroe et al, 1997;Hamann and di Vadi, 1999;Ware et al, 2003;Rudich et al, 2003;Ware and Beaulieu, 2005;Berlach et al, 2006; reviewed in Burns and Ineck, 2006) (Table 1). The results of randomized studies conducted before 1999 on the analgesic effect of orally administered synthetic cannabinoids in patients with postoperative, post-traumatic, cancer, or spastic pain had been subjected to a meta-analysis.…”
Section: B Pain and Inflammationmentioning
confidence: 99%
“…Another potential limitation to the use of cannabinoids for pain is the development of tolerance and dependence, an issue that impacts the therapeutic potential of opioids. Although tolerance to the analgesic effects of cannabinoids may require escalating doses over time, CB1 agonists have a favorable safety profile (Burns and Ineck, 2006) relative to opioids, which can have respiratory depressant effects at high doses (Smith and Bruckenthal, 2010). A primary caveat of these findings is that the study population consisted of daily marijuana smokers; this study limitation should be considered when interpreting the findings and placing them within the context of the potential therapeutic feasibility of cannabinoids.…”
Section: Discussionmentioning
confidence: 96%
“…Although cannabinoid analgesia has been reasonably well studied in humans (Pertwee, 2001;Burns et al, 2006;Huskey, 2006;Manzanares et al, 2006) the exact contributions of the cannabinoid receptors is still under investigation. Many preclinical studies have shown that cannabinoids produce analgesia by acting in both the central and peripheral nervous system (Pertwee, 2001), via CB1 receptors in the brain, but also by both CB1 and CB2 receptors in the spinal cord and periphery (Agarwal et al, 2007).…”
Section: Cannabinoid Receptorsmentioning
confidence: 99%